Persistent Gliosis Interferes with Neurogenesis in Organotypic Hippocampal Slice Cultures - Gerlach, Johannes; Donkels, Catharina; Münzner, Gert; Haas, Carola A. (Frontiers in Cellular Neuroscience, 2016)
Neurogenesis in the adult hippocampus has become an intensively investigated research topic, as it is essential for proper hippocampal function and considered to bear therapeutic potential for the replacement of pathologically lost neurons. On the other hand, neurogenesis itself is frequently affected by CNS insults. To identify processes leading to the disturbance of neurogenesis, we made use of organotypic hippocampal slice cultures (OHSC), which, for unknown reasons, lose their neurogenic potential during cultivation. In the present study, we show by BrdU/Prox1 double-immunostaining that the generation of new granule cells drops by 90% during the first week of cultivation. Monitoring neurogenesis dynamically in OHSC from POMC-eGFP mice, in which immature granule cells are endogenously labeled, revealed a gradual decay of the eGFP signal, reaching 10% of initial values within seven days of cultivation. Accordingly, RT-qPCR analysis showed the downregulation of the neurogenesis-related genes doublecortin and Hes5, a crucial target of the stem cell-maintaining Notch signaling pathway. In parallel, we demonstrate a strong and long-lasting activation of astrocytes and microglial cells, both, morphologically and on the level of gene expression. Enhancement of astroglial activation by treating OHSC with ciliary neurotrophic factor (CNTF) accelerated the loss of neurogenesis, whereas treatment with indomethacin or an antagonist of the purinergic P2Y12 receptor exhibited potent protective effects on the neurogenic outcome. Therefore, we conclude that OHSC rapidly lose their neurogenic capacity due to persistent inflammatory processes taking place after the slice preparation. As inflammation is also considered to affect neurogenesis in many CNS pathologies, OHSC appear as a useful tool to study this interplay and its molecular basis. Furthermore, we propose that modification of glial activation might bear the therapeutic potential of enabling neurogenesis under neuropathological conditions.